Lithium-doped porous carbon material, lithium-doped silicon-carbon composite material, preparation method and application thereof, and lithium ion battery
By doping lithium into the porous carbon material and depositing silicon, lithium-doped silicon-carbon composite material is prepared, which solves the problem of insufficient capacity and efficiency of existing porous carbon materials, and achieves efficient performance of the negative electrode material of lithium-ion batteries.
Patent Information
- Application Number
- CN202510386694.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-03-31
AI Technical Summary
The existing porous carbon materials have low theoretical capacity and low initial Coulomb efficiency in lithium-ion batteries, making it difficult to meet the requirements of high energy and high power density.
By mixing the lithium source, phenolic compounds with solvents for modification treatment, then performing addition-polycondensation reaction to generate lithium-modified phenolic resin, and a lithium-doped porous carbon material is prepared by pyrolysis and activation treatment, and finally, silicon is deposited on its surface to obtain a lithium-doped silicon-carbon composite material.
The prepared lithium-doped silicon-carbon composite material, as the negative electrode material of lithium-ion batteries, has high initial Coulomb efficiency, good rate performance and cycling performance.
Smart Images

Figure CN119911904A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon materials, and in particular to lithium-doped porous carbon materials, lithium-doped silicon-carbon composite materials, preparation methods and applications thereof, and lithium-ion batteries. Background Art
[0002] With the reduction of fossil energy and the increase in demand for green energy, the development of renewable energy and clean energy is the core of solving the future energy crisis. Porous carbon materials usually have excellent properties such as developed pores, high specific surface area and unique electronic conductivity, and are widely used as negative electrode materials for lithium batteries. However, porous carbon materials have low theoretical capacity and low initial coulomb efficiency, which is far from meeting the requirements of high energy and high power density. Summary of the invention
[0003] The purpose of the present invention is to provide a lithium-doped porous carbon material, a lithium-doped silicon-carbon composite material, and a preparation method and application thereof in a lithium-ion battery. The lithium-doped silicon-carbon composite material is obtained by depositing silicon on the lithium-doped porous carbon material provided by the present invention. The lithium-doped silicon-carbon composite material is used as a negative electrode material for a lithium-ion battery, which has a higher initial coulombic efficiency and better rate performance and cycle performance.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for preparing a lithium-doped porous carbon material, comprising the following steps: Mixing a lithium source, a first phenolic compound and a first solvent, and performing a modification treatment to obtain a modified product liquid; The modified product liquid, the aldehyde compound, the second phenolic compound and the second solvent are mixed to carry out addition-condensation reaction to obtain a lithium-modified phenolic resin; The lithium-modified phenolic resin is subjected to pyrolysis treatment and activation treatment in sequence to obtain the lithium-doped porous carbon material.
[0005] Preferably, the lithium source is lithium hydroxide; the first phenolic compound and the second phenolic compound are independently selected from one or more of phenol, cresol, xylenol, hydroquinone and resorcinol; the aldehyde compound includes one or more of formaldehyde, acetaldehyde and furfural; the first solvent and the second solvent are water.
[0006] Preferably, the ratio of the lithium source, the first phenolic compound and the first solvent is 0.17-0.23 mol: 0.17-0.23 mol: 90-110 g; the temperature of the modification treatment is 75-85° C., and the time is 22-26 h; The dosage ratio of the modified product liquid, the aldehyde compound and the second phenolic compound is 25~35mL: 0.8~0.9mol: 0.17~0.23mol; the addition-condensation reaction includes sequentially carrying out a first stage reaction and a second stage reaction; the temperature of the first stage reaction is 40~50°C and the time is 4~6h; the temperature of the second stage reaction is 90~100°C and the time is 45~50h.
[0007] Preferably, the temperature of the pyrolysis treatment is 650-750°C, and the holding time is 1.5-2.5h; the heating rate to the temperature required for the pyrolysis treatment is 8-12°C / min; the pyrolysis treatment is carried out in a protective atmosphere; The temperature of the activation treatment is 950-1000°C, and the holding time is 7-9h; the heating rate to the temperature required for the activation treatment is 8-12°C / min; the activation treatment is carried out in a CO2 atmosphere.
[0008] The present invention provides a lithium-doped porous carbon material prepared by the preparation method described in the above technical solution.
[0009] Preferably, the specific surface area of the lithium-doped porous carbon material is 1500-2200 m 2 / g, pore volume is 0.5~0.8cm 3 / g; the volume percentage of pores with a pore size of less than 2 nm in the lithium-doped porous carbon material is 80-90% of all pores, and the volume percentage of pores with a pore size of 2-10 nm is 6-11% of all pores.
[0010] The present invention provides a lithium-doped silicon-carbon composite material, comprising a lithium-doped porous carbon material and silicon deposited on the lithium-doped porous carbon material. The lithium-doped porous carbon material is the lithium-doped porous carbon material described in the above technical solution.
[0011] The present invention provides a method for preparing the lithium-doped silicon-carbon composite material described in the above technical solution, comprising the following steps: In the presence of a gaseous silicon source and a carrier gas, silicon is deposited on the surface of the lithium-doped porous carbon material to obtain the lithium-doped silicon-carbon composite material.
[0012] The present invention provides the use of the lithium-doped silicon-carbon composite material described in the above technical solution or the lithium-doped silicon-carbon composite material prepared by the preparation method described in the above technical solution in negative electrode materials for lithium-ion batteries.
[0013] The present invention provides a lithium-ion battery, comprising a negative electrode, a positive electrode, an electrolyte and a separator, wherein the negative electrode comprises a substrate and a negative electrode material loaded on the surface of the substrate, and the negative electrode material comprises the lithium-doped silicon-carbon composite material described in the above technical solution or the lithium-doped silicon-carbon composite material prepared by the preparation method described in the above technical solution.
[0014] Beneficial effects: The present invention provides a method for preparing a lithium-doped porous carbon material, comprising the following steps: mixing a lithium source, a first phenolic compound and a first solvent, performing a modification treatment, and obtaining a modified product liquid; mixing the modified product liquid, an aldehyde compound, a second phenolic compound and a second solvent, and performing an addition-polycondensation reaction to obtain a lithium-modified phenolic resin; and sequentially performing a pyrolysis treatment and an activation treatment on the lithium-modified phenolic resin to obtain the lithium-doped porous carbon material. The present invention adopts lithium as a doping element, and polycondenses it into a phenolic resin structure by an in-situ polymerization method to realize in-situ doping of lithium elements, thereby preparing a lithium-modified phenolic resin, and on this basis, preparing a lithium-doped porous carbon material by pyrolysis treatment and activation treatment. The lithium-doped porous carbon material prepared by the present invention has developed pores and a large specific surface area. After depositing silicon on the lithium-doped porous carbon material provided by the present invention, a lithium-doped silicon-carbon composite material is obtained. The lithium-doped silicon-carbon composite material is used as a negative electrode material of a lithium-ion battery, and has excellent electrochemical properties, a high initial coulombic efficiency, and good rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a SEM image of the lithium-doped porous carbon material prepared in Example 1; Figure 2 This is a SEM image of the porous carbon material prepared in Comparative Example 1; Figure 3 This is a first cycle charge and discharge voltage curve of a lithium ion battery assembled using the silicon-carbon composite material prepared using the porous carbon material in Example 1. DETAILED DESCRIPTION
[0016] The present invention provides a method for preparing a lithium-doped porous carbon material, comprising the following steps: Mixing a lithium source, a first phenolic compound and a first solvent, and performing a modification treatment to obtain a modified product liquid; The modified product liquid, the aldehyde compound, the second phenolic compound and the second solvent are mixed to carry out addition-condensation reaction to obtain a lithium-modified phenolic resin; The lithium-modified phenolic resin is subjected to pyrolysis treatment and activation treatment in sequence to obtain the lithium-doped porous carbon material.
[0017] The present invention adopts phenolic resin as carbon source to prepare lithium-doped porous carbon material. Phenolic resin is a kind of polymer material obtained by polycondensation reaction of phenolic compounds and aldehyde compounds. Pyrolysis treatment is carried out to realize carbonization, and then pores are made by activation treatment to obtain phenolic resin-based porous carbon material. Phenolic compounds and aldehyde compounds are widely present in nature, are relatively easy to obtain and are cheap, and are convenient to realize large-scale production of carbon materials. Phenolic resin has excellent thermal stability, can maintain its original morphology after carbonization, has good structural stability, has abundant functional groups, and can achieve the purpose of introducing metal ions by electrostatic adsorption. In addition, phenolic resin also has extremely high residual carbon content, and the sample after carbonization has a higher yield. The lithium-doped porous carbon material prepared based on phenolic resin in the present invention is deposited with silicon to obtain a lithium-doped silicon-carbon composite material. The lithium-doped silicon-carbon composite material is used as a negative electrode material of a lithium-ion battery and has excellent electrochemical properties. On the one hand, the lithium-doped silicon-carbon composite material can greatly improve the rate performance and cycle performance of the lithium-ion battery. Specifically, due to the high specific surface area of the porous carbon material and the additional active sites brought by lithium doping, more lithium ions can be combined; on the other hand, the lithium-doped silicon-carbon composite material can reduce the AC impedance value of the lithium-ion battery. Specifically, good conductivity makes the transmission of ions in the electrode smoother, which can reduce energy loss, thereby helping to improve the charge and discharge efficiency of the lithium-ion battery. The carbon-based material not only acts as a buffer to adapt to volume expansion, but also prevents the aggregation of doped particles. Therefore, the present invention successfully incorporates lithium into the porous carbon material to prepare a lithium-doped porous carbon material, and on this basis, deposits silicon to obtain a lithium-doped silicon-carbon composite material. The lithium-doped silicon-carbon composite material is used as a negative electrode material in a lithium-ion battery and has excellent electrochemical properties, a high initial coulomb efficiency, and good rate performance and cycle performance. The method of the present invention is described in detail below.
[0018] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art or are prepared by methods well known to those skilled in the art.
[0019] The present invention mixes a lithium source, a first phenolic compound and a first solvent, performs a modification treatment, and obtains a modified product liquid. As an embodiment of the present invention, the lithium source can be lithium hydroxide, specifically lithium hydroxide monohydrate; the first phenolic compound can be selected from one or more of phenol, cresol, xylenol, hydroquinone and resorcinol, specifically phenol, cresol, xylenol, hydroquinone or resorcinol; the first solvent can be water; the amount ratio of the lithium source, the first phenolic compound and the first solvent can be 0.17~0.23mol: 0.17~0.23mol: 90~110g, specifically 0.19~0.20mol: 0.19~0.20mol: 100g.
[0020] As an embodiment of the present invention, the temperature of the modification treatment can be 75-85°C, further can be 78-82°C, specifically can be 80°C; the time can be 22-26h, further can be 23-25h, specifically can be 24h; the modification treatment can be carried out under stirring conditions, and the present invention has no special limitation on the stirring rate, as long as the modification treatment is carried out smoothly. In an embodiment of the present invention, during the modification treatment, the lithium source reacts with the first phenolic compound in the first solvent. Taking phenol as an example, the hydroxyl group in the phenol removes the hydrogen atom to form a negative monovalent group, which has a negative charge and combines with a lithium ion with a positive charge to form phenoxy lithium, which is convenient for the subsequent in-situ doping of lithium through addition-condensation reaction to prepare a lithium-modified phenolic resin.
[0021] After obtaining the modified product liquid, the present invention mixes the modified product liquid, the aldehyde compound, the second phenolic compound and the second solvent to carry out addition-condensation reaction to obtain the lithium-modified phenolic resin. As an embodiment of the present invention, the aldehyde compound may include one or more of formaldehyde, acetaldehyde and furfural, specifically formaldehyde, acetaldehyde or furfural; the second phenolic compound may be selected from one or more of phenol, cresol, xylenol, hydroquinone and resorcinol, specifically phenol, cresol, xylenol, hydroquinone or resorcinol, and the second phenolic compound is preferably the same as the first phenolic compound; the second solvent may be water; the amount ratio of the modified product liquid, the aldehyde compound and the second phenolic compound may be 25~35mL: 0.8~0.9mol: 0.17~0.23mol; specifically 30mL: 0.84~0.85mol: 0.19~0.20mol; the amount ratio of the second phenolic compound to the second solvent may be 0.17~0.23mol: 200~220g, specifically 0.19~0.20mol: 208~210g.
[0022] As an embodiment of the present invention, the aldehyde compound, the second phenolic compound and the second solvent are mixed, and then the modified product liquid is added to carry out addition-polycondensation reaction. As an embodiment of the present invention, the addition-polycondensation reaction includes sequentially carrying out the first stage reaction and the second stage reaction. As an embodiment of the present invention, the temperature of the first stage reaction can be 40~50℃, specifically 45℃; the time can be 4~6h, specifically 5h; the first stage reaction can be carried out under stirring conditions, and the present invention has no special restrictions on the stirring rate, as long as the first stage reaction is carried out smoothly. As an embodiment of the present invention, the temperature of the second stage reaction can be 90~100℃, specifically 95℃; the time can be 45~50h, specifically 48h; the second stage reaction can be carried out under stirring conditions, and the present invention has no special restrictions on the stirring rate, as long as the second stage reaction is carried out smoothly. In the embodiment of the present invention, taking the synthesis of lithium-modified phenolic resin using phenol, phenoxy lithium and formaldehyde as an example, first, phenol and formaldehyde are subjected to a first-stage reaction under relatively low temperature conditions, during which phenol and formaldehyde undergo addition reaction to generate a variety of hydroxymethylphenols, i.e., the product is a mixture of monophenol alcohol and polyphenol alcohol. When the temperature rises (e.g., above 60° C.), a second-stage reaction is carried out, during which addition reaction and polycondensation reaction are carried out simultaneously. The phenoxy lithium generated by the modification treatment continuously undergoes polycondensation reaction with the monophenol alcohol and the polyphenol alcohol during the reaction process, so that the molecular weight of the resin is continuously increased, and finally a lithium-modified phenolic resin is obtained.
[0023] As an embodiment of the present invention, after the addition-polycondensation reaction, the precipitate generated in the collection system is dried and crushed in sequence to obtain a lithium-modified phenolic resin powder, and then the lithium-modified phenolic resin powder is subjected to pyrolysis treatment and activation treatment in sequence to obtain the lithium-doped porous carbon material. The present invention does not specifically limit the conditions for the drying and crushing, and conditions familiar to those skilled in the art can be used.
[0024] As an embodiment of the present invention, the temperature of the pyrolysis treatment can be 650~750℃, further can be 680~720℃, specifically can be 700℃; the holding time can be 1.5~2.5h, specifically can be 2h; the heating rate to the temperature required for the pyrolysis treatment can be 8~12℃ / min, specifically can be 10℃ / min; the pyrolysis treatment can be carried out in a protective atmosphere, the protective atmosphere can be argon, and the flow rate of the argon can be 8~12mL / min, specifically can be 10mL / min. As an embodiment of the present invention, the pyrolysis treatment can be carried out in a tubular furnace. In an embodiment of the present invention, during the pyrolysis treatment, the lithium-modified phenolic resin is carbonized to form pyrolytic carbon.
[0025] As an embodiment of the present invention, the temperature of the activation treatment can be 950~1000℃, further can be 970~980℃, specifically can be 975℃; the insulation time can be 7~9h, further can be 7.5~8.5h, specifically can be 8h; the heating rate to the temperature required for the activation treatment can be 8~12℃ / min, specifically can be 10℃ / min. As an embodiment of the present invention, the activation treatment can be carried out in a CO2 atmosphere, and based on the mass of pyrolytic carbon, the flow rate of CO2 can be 4~5mL / min / g, specifically can be 4.51mL / min / g; in the embodiment of the present invention, taking 6g of pyrolytic carbon as an example, the flow rate of CO2 can be 27.06mL / min. As an embodiment of the present invention, the activation treatment can be carried out in a tubular furnace. In the embodiment of the present invention, a CO2 activation method is adopted, in which CO2 is introduced to react with pyrolytic carbon under high temperature conditions to achieve pore formation in pyrolytic carbon. The pore structure and specific surface area of the lithium-doped porous carbon material can be effectively regulated to prepare a lithium-doped porous carbon material with a rich pore structure and excellent electrochemical properties.
[0026] The present invention provides a lithium-doped porous carbon material prepared by the preparation method of the above technical solution. As an embodiment of the present invention, the specific surface area of the lithium-doped porous carbon material can be 1500~2200m 2 / g, and can be further 1520~2150m 2 / g, specifically 1530.6774, 1762.3424m 2 / g, 1811.9925m 2 / g, 1918.8347m 2 / g, 2026.5146m 2 / g or 2130.1523m 2 / g; the pore volume can be 0.5~0.8cm 3 / g, specifically 0.5485m 2 / g, 0.6414m 2 / g, 0.6621m 2 / g, 0.7325m 2 / g, 0.7750m 2 / g or 0.7972m 2 / g; the volume percentage of pores with a pore size less than 2 nm in the lithium-doped porous carbon material can be 80-90%, specifically 83.78%, 84.56%, 85.86%, 85.95%, 88.19% or 89.76%; the volume percentage of pores with a pore size of 2-10 nm can be 6-11%, specifically 6.03%, 6.94%, 8.28%, 8.66%, 8.96% or 10.52%; the lithium-doped porous carbon material also has remaining pores with a pore size greater than 10 nm.
[0027] The present invention provides a lithium-doped silicon-carbon composite material, comprising a lithium-doped porous carbon material and silicon deposited on the lithium-doped porous carbon material. The lithium-doped porous carbon material is the lithium-doped porous carbon material described in the above technical solution.
[0028] As an embodiment of the present invention, the content of silicon in the lithium-doped silicon-carbon composite material can be 40-60wt%, specifically 40wt%, 45wt%, 48wt%, 50wt%, 52wt%, 55wt% or 60wt%.
[0029] The present invention provides a method for preparing the lithium-doped silicon-carbon composite material described in the above technical solution, comprising the following steps: In the presence of a gaseous silicon source and a carrier gas, silicon is deposited on the surface of the lithium-doped porous carbon material to obtain the lithium-doped silicon-carbon composite material.
[0030] As an embodiment of the present invention, the gas silicon source can be silane, specifically monosilane; the carrier gas can be helium. As an embodiment of the present invention, the silicon deposition can be carried out in a CVD furnace, and the rotation speed of the CVD furnace during the silicon deposition process can be 15-25rpm, specifically 20rpm; based on the mass of the lithium-doped porous carbon material of 25g, the flow rate of the carrier gas can be 4.5-5.5L / min, specifically 5L / min; the flow rate of the silane can be 0.08-0.12L / min, specifically 0.1L / min. As an embodiment of the present invention, the conditions for the silicon deposition include: the deposition temperature can be 500-600℃, specifically 500℃, 530℃, 550℃, 580℃ or 600℃; the deposition time can be 1-9h, specifically 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h or 9h. In an embodiment of the present invention, the lithium-doped porous carbon material can be placed in a CVD furnace and its rotation speed can be set to 15-25 rpm, a carrier gas is introduced at a flow rate of 4.5-5.5 L / min, the temperature is raised to the temperature required for silicon deposition in the carrier gas environment, the carrier gas flow rate is maintained, and a gas silicon source is introduced at a flow rate of 0.08-0.12 L / min for silicon deposition. As an embodiment of the present invention, after the silicon deposition, it can also include: stopping the introduction of the gas silicon source, maintaining the carrier gas flow rate to remove excess gas silicon source, and then introducing acetylene gas at a flow rate of 0.18-0.22 L / min (specifically 0.2 L / min) for deposition. As an embodiment of the present invention, the conditions for deposition using acetylene gas include: the deposition temperature can be 500-600°C, specifically 500°C, 530°C, 550°C, 580°C or 600°C; the deposition time can be 1-5h, specifically 1h, 2h, 3h, 4h or 5h.
[0031] The present invention provides the use of the lithium-doped silicon-carbon composite material described in the above technical solution or the lithium-doped silicon-carbon composite material prepared by the preparation method described in the above technical solution in negative electrode materials for lithium-ion batteries.
[0032] The present invention provides a lithium-ion battery, comprising a negative electrode, a positive electrode, an electrolyte and a separator, wherein the negative electrode comprises a substrate and a negative electrode material loaded on the surface of the substrate, and the negative electrode material comprises the lithium-doped silicon-carbon composite material described in the above technical solution or the lithium-doped silicon-carbon composite material prepared by the preparation method described in the above technical solution.
[0033] As an embodiment of the present invention, the negative electrode includes a substrate and a negative electrode material loaded on the surface of the substrate; the substrate in the negative electrode can be a copper foil; the raw materials for preparing the negative electrode material can include lithium-doped silicon-carbon composite material, Super P, carbon nanotubes, carboxymethyl cellulose and styrene-butadiene rubber composite binder. The present invention does not specifically limit the amount of each raw material for preparing the negative electrode material, and the amount familiar to those skilled in the art can be used. In the embodiment of the present invention, the silicon-carbon composite material is specifically mixed with Super P, carbon nanotubes, carboxymethyl cellulose and styrene-butadiene rubber composite binder, the obtained mixture is coated on the surface of the substrate, and the negative electrode is obtained after drying.
[0034] As an embodiment of the present invention, the positive electrode is specifically a metal lithium sheet.
[0035] As an embodiment of the present invention, the electrolyte may be a LiPF6 solution, the concentration of LiPF6 in the LiPF6 solution may be 1 mol / L, the solvent in the LiPF6 solution may be diethyl carbonate, dimethyl carbonate and ethylene carbonate, and the volume ratio of diethyl carbonate, dimethyl carbonate and ethylene carbonate may be 1:1:1.
[0036] The present invention has no special limitation on the diaphragm, and any diaphragm well known to those skilled in the art may be used.
[0037] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1 18 g of phenol, 8.04 g of lithium hydroxide monohydrate and 100 g of water were mixed, and the mixture was subjected to a modification treatment at 80° C. with stirring for 24 h to obtain a modified product liquid; 18 g of phenol, 25.29 g of formaldehyde and 208.71 g of water were mixed, and then 30 mL of the modified product solution was added, and the first stage reaction was carried out at 45° C. and under stirring conditions for 5 h, and then the temperature was increased, and the second stage reaction was carried out at 95° C. and under stirring conditions for 48 h; after the second stage reaction was completed, the precipitate generated in the collection system was lithium-modified phenolic resin; The lithium-modified phenolic resin is dried and then crushed to obtain a lithium-modified phenolic resin powder, and then the lithium-modified phenolic resin powder is heated from room temperature to 700° C. at a heating rate of 10° C. / min under an argon gas flow rate of 10 mL / min and kept at this temperature for pyrolysis treatment for 2 hours to obtain pyrolytic carbon; Take 6 g of the pyrolytic carbon, and heat it from room temperature to 975° C. at a heating rate of 10° C. / min under a CO2 flow rate of 27.06 mL / min and keep it warm for 8 hours for activation treatment to obtain a lithium-doped porous carbon material.
[0039] Example 2 21.06 g of resorcinol, 8.04 g of lithium hydroxide monohydrate and 100 g of water were mixed, and the mixture was subjected to a modification treatment at 80° C. with stirring for 24 h to obtain a modified product liquid; 21.06 g of resorcinol, 25.29 g of formaldehyde and 208.71 g of water were mixed, and then 30 mL of the modified product solution was added, and the first stage reaction was carried out at 45° C. and stirred for 5 h, and then the temperature was increased, and the second stage reaction was carried out at 95° C. and stirred for 48 h to obtain a lithium-modified phenolic resin; The lithium-modified phenolic resin was subjected to pyrolysis treatment and activation treatment in sequence according to the method of Example 1 to obtain a lithium-doped porous carbon material.
[0040] Example 3 23.36 g of xylenol, 8.04 g of lithium hydroxide monohydrate and 100 g of water were mixed, and the mixture was subjected to a modification treatment at 80° C. with stirring for 24 h to obtain a modified product liquid; 23.36 g of xylenol, 25.29 g of formaldehyde and 208.71 g of water were mixed, and then 30 mL of the modified product solution was added, and the first stage reaction was carried out at 45° C. and stirred for 5 h, and then the temperature was increased, and the second stage reaction was carried out at 95° C. and stirred for 48 h to obtain a lithium-modified phenolic resin; The lithium-modified phenolic resin was subjected to pyrolysis treatment and activation treatment in sequence according to the method of Example 1 to obtain a lithium-doped porous carbon material.
[0041] Example 4 21.06 g of resorcinol, 8.04 g of lithium hydroxide monohydrate and 100 g of water were mixed, and the mixture was subjected to a modification treatment at 80° C. with stirring for 24 h to obtain a modified product liquid; 21.06 g of resorcinol, 37.10 g of acetaldehyde and 208.71 g of water were mixed, and then 30 mL of the modified product solution was added, and the first stage reaction was carried out at 45° C. and stirred for 5 h, and then the temperature was increased, and the second stage reaction was carried out at 95° C. and stirred for 48 h to obtain a lithium-modified phenolic resin; The lithium-modified phenolic resin was subjected to pyrolysis treatment and activation treatment in sequence according to the method of Example 1 to obtain a lithium-doped porous carbon material.
[0042] Example 5 18 g of phenol, 8.04 g of lithium hydroxide monohydrate and 100 g of water were mixed, and the mixture was subjected to a modification treatment at 80° C. with stirring for 24 h to obtain a modified product liquid; 18 g of phenol, 37.10 g of acetaldehyde and 208.71 g of water were mixed, and then 30 mL of the modified product solution was added, and the first stage reaction was carried out at 45° C. and stirred for 5 h, and then the temperature was increased, and the second stage reaction was carried out at 95° C. and stirred for 48 h to obtain a lithium-modified phenolic resin; The lithium-modified phenolic resin was subjected to pyrolysis treatment and activation treatment in sequence according to the method of Example 1 to obtain a lithium-doped porous carbon material.
[0043] Example 6 18 g of phenol, 8.04 g of lithium hydroxide monohydrate and 100 g of water were mixed, and the mixture was subjected to a modification treatment at 80° C. with stirring for 24 h to obtain a modified product liquid; 18 g of phenol, 80.92 g of furfural and 208.71 g of water were mixed, and then 30 mL of the modified product solution was added, and the first stage reaction was carried out at 45° C. and stirred for 5 h, and then the temperature was increased, and the second stage reaction was carried out at 95° C. and stirred for 48 h to obtain a lithium-modified phenolic resin; The lithium-modified phenolic resin was subjected to pyrolysis treatment and activation treatment in sequence according to the method of Example 1 to obtain a lithium-doped porous carbon material.
[0044] Comparative Example 1 Mix 18g of phenol, 25.29g of formaldehyde and 208.71g of water, carry out the first stage reaction at 45°C with stirring for 5 hours, then increase the temperature, carry out the second stage reaction at 95°C with stirring for 48 hours to obtain a phenolic resin; then, refer to the method of Example 1 to perform pyrolysis treatment and activation treatment on the phenolic resin in sequence to obtain a porous carbon material.
[0045] Comparative Example 2 Mix 21.06g of resorcinol, 25.29g of formaldehyde and 208.71g of water, carry out the first stage reaction at 45°C with stirring for 5 hours, then increase the temperature, carry out the second stage reaction at 95°C with stirring for 48 hours to obtain a phenolic resin; then, refer to the method of Example 1 to perform pyrolysis treatment and activation treatment on the phenolic resin in sequence to obtain a porous carbon material.
[0046] Comparative Example 3 Mix 23.36g of xylenol, 25.29g of formaldehyde and 208.71g of water, carry out the first stage reaction at 45°C with stirring for 5 hours, then increase the temperature, carry out the second stage reaction at 95°C with stirring for 48 hours to obtain phenolic resin; then, refer to the method of Example 1 to perform pyrolysis treatment and activation treatment on the phenolic resin in sequence to obtain a porous carbon material.
[0047] Test Example 1 Figure 1 This is a SEM image of the lithium-doped porous carbon material prepared in Example 1. The results show that there are no obvious holes on the surface of the lithium-doped porous carbon material prepared in Example 1, but there are relatively more pits, which is caused by lithium doping.
[0048] Figure 2 This is a SEM image of the porous carbon material prepared in Comparative Example 1. The results show that the surface of the porous carbon material prepared in Comparative Example 1 is substantially dense and smooth, and no large holes or pits are found.
[0049] The porous carbon materials prepared in the examples and comparative examples were subjected to performance tests, and the specific results are shown in Table 1. As can be seen from Table 1, in the lithium-doped porous carbon materials prepared in Examples 1 to 6, the specific surface area and pore volume of the porous carbon materials are slightly reduced due to the embedding of lithium elements into the carbon skeleton.
[0050] Table 1 Performance test results of porous carbon materials in examples and comparative examples
[0051] Test Example 2 The porous carbon materials prepared in each embodiment and comparative example were subjected to silicon deposition to prepare a silicon-carbon composite material, and the specific steps are as follows: 25 g of the porous carbon material was placed in a CVD furnace with a rotation speed of 20 rpm, helium was introduced at a flow rate of 5 L / min, the temperature was raised to 600°C in a helium atmosphere, the helium flow rate was maintained and monosilane gas was introduced at a flow rate of 0.1 L / min, and chemical vapor deposition was carried out for 1 hour. After the deposition was completed, helium was continuously introduced at a flow rate of 5 L / min to remove excess monosilane gas, and acetylene gas was introduced at a flow rate of 0.2 L / min, and vapor deposition was carried out at 600°C for 1 hour to obtain the silicon-carbon composite material, in which the silicon content of the silicon-carbon composite material was 50 wt%.
[0052] The silicon-carbon composite material is mixed with Super P, carbon nanotubes, carboxymethyl cellulose and styrene-butadiene rubber composite binder respectively, and the obtained mixture is coated on the surface of copper foil, and dried to obtain a negative electrode; a metal lithium sheet is used as a positive electrode; a LiPF6 solution with a concentration of 1 mol / L is used as an electrolyte (the solvent is diethyl carbonate, dimethyl carbonate and ethylene carbonate, and the volume ratio of the three is 1:1:1); a diaphragm and the negative electrode, positive electrode and electrolyte are assembled together to obtain a lithium-ion battery, and a LAND charge and discharge tester is used to perform a charge and discharge test on the lithium-ion battery under the conditions of a current density of 0.1C and a voltage range of 0.005~1.5V. The specific results are as follows Figure 3 And as shown in Table 2.
[0053] Figure 3 The first cycle charge and discharge voltage curve of the lithium ion battery assembled by using the silicon-carbon composite material prepared by the porous carbon material in Example 1 is shown in Table 2. As shown in Table 2, compared with the silicon-carbon composite material prepared by using the porous carbon material in Comparative Examples 1 to 3, the lithium-doped silicon-carbon composite material prepared by using the lithium-doped porous carbon material in Examples 1 to 6 has excellent electrochemical performance, and the reversible specific capacity, first efficiency and 100-cycle capacity retention rate are all higher.
[0054] Table 2 Performance test results of lithium-ion batteries assembled using various silicon-carbon composite materials
[0055] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a lithium-doped porous carbon material, comprising the following steps: Mixing a lithium source, a first phenolic compound and a first solvent, and performing a modification treatment to obtain a modified product liquid; The modified product liquid, the aldehyde compound, the second phenolic compound and the second solvent are mixed to carry out addition-condensation reaction to obtain a lithium-modified phenolic resin; The lithium-modified phenolic resin is subjected to pyrolysis treatment and activation treatment in sequence to obtain the lithium-doped porous carbon material.
2. The preparation method according to claim 1, characterized in that: The lithium source is lithium hydroxide; the first phenolic compound and the second phenolic compound are independently selected from one or more of phenol, cresol, xylenol, hydroquinone and resorcinol; the aldehyde compound includes one or more of formaldehyde, acetaldehyde and furfural; the first solvent and the second solvent are water.
3. The preparation method according to claim 1 or 2, characterized in that: The lithium source, the first phenolic compound and the first solvent are used in a ratio of 0.17-0.23 mol: 0.17-0.23 mol: 90-110 g; the modification treatment is carried out at a temperature of 75-85° C. for 22-26 h; The dosage ratio of the modified product liquid, the aldehyde compound and the second phenolic compound is 25~35mL: 0.8~0.9mol: 0.17~0.23mol; the addition-condensation reaction includes sequentially carrying out a first stage reaction and a second stage reaction; the temperature of the first stage reaction is 40~50°C and the time is 4~6h; the temperature of the second stage reaction is 90~100°C and the time is 45~50h.
4. The preparation method according to claim 1 or 2, characterized in that: The temperature of the pyrolysis treatment is 650-750°C, and the holding time is 1.5-2.5h; the heating rate to the temperature required for the pyrolysis treatment is 8-12°C / min; the pyrolysis treatment is carried out in a protective atmosphere; The temperature of the activation treatment is 950-1000°C, and the holding time is 7-9h; the heating rate to the temperature required for the activation treatment is 8-12°C / min; the activation treatment is carried out in a CO2 atmosphere.
5. The lithium-doped porous carbon material prepared by the preparation method according to any one of claims 1 to 4.
6. The lithium-doped porous carbon material according to claim 5, characterized in that: The specific surface area of the lithium-doped porous carbon material is 1500-2200 m 2 / g, pore volume is 0.5~0.8cm 3 / g; the volume percentage of pores with a pore size of less than 2 nm in the lithium-doped porous carbon material is 80-90% of all pores, and the volume percentage of pores with a pore size of 2-10 nm is 6-11% of all pores.
7. A lithium-doped silicon-carbon composite material, comprising a lithium-doped porous carbon material and silicon deposited on the lithium-doped porous carbon material, wherein the lithium-doped porous carbon material is the lithium-doped porous carbon material according to claim 5 or 6.
8. The method for preparing the lithium-doped silicon-carbon composite material according to claim 7, comprising the following steps: In the presence of a gaseous silicon source and a carrier gas, silicon is deposited on the surface of the lithium-doped porous carbon material to obtain the lithium-doped silicon-carbon composite material.
9. Use of the lithium-doped silicon-carbon composite material according to claim 7 or the lithium-doped silicon-carbon composite material prepared by the preparation method according to claim 8 in negative electrode materials for lithium-ion batteries.
10. A lithium-ion battery comprising a negative electrode, a positive electrode, an electrolyte and a separator, wherein the negative electrode comprises a substrate and a negative electrode material loaded on the surface of the substrate, and the negative electrode material comprises the lithium-doped silicon-carbon composite material according to claim 7 or the lithium-doped silicon-carbon composite material prepared by the preparation method according to claim 8.
Citation Information
Patent Citations
Porous carbon material, process for producing the same, adsorbent, mask, adsorbent sheet and supporting member
CN103936003A
Metal-doped porous carbon and silicon carbon material and preparation method thereof
CN118419892A
Long-circulation silicon-carbon negative electrode material and preparation method thereof
CN118693270A
Preparation method of heterogeneous element doped carbon material
CN118754119A
Metal-doped porous carbon, preparation method and application
CN119162484A
Cited By
Solid electrolyte doped silicon-carbon composite material, preparation method and application thereof
CN121076100A